Between Isolation and Cultural Engagement: An Ecclesiological Analysis of Romanian Evangelical Churches in the European Diaspora - Fodorean, Daniel (Bogoslovs'ki rozdymi, 2025)
All immigrants, wherever they come from and in the specific socio-cultural context to which they immigrate, experience a never-ending struggle between the cultural imprint of their own country of origin and a process of acculturation to these societies. Indeed, the migratory experience entails simultaneously inhabiting one's "homeland" and the place where one wants to try to "forge" a new home. But moving isn't really over until you become part of the society to which you are now connected. Here, the question of the Church assumes special significance, and this precisely is her transcultural vocation. This leads us to the underlying question: how can the Church overcome ethnic and cultural barriers to fulfill its divine commission in a socio-cultural environment other than itsmotherland? This paper attempts to offer a response through the analysis of a specific case: the Romanian evangelical diaspora in Europe. Based on a questionnaire, the study examined the extent to which Romanian Evangelical Christians are integrated into their host culture and how they view the Church's relationship with culture, as well as sought possible ways to develop a relevant, contextualized Romanian Evangelical Church under local cultural norms.